A Multiscale Homogenization Scheme With the Virtual Element Method - Lopez Rivarola, Felipe (2018)
Evaluations and predictions of the behaviour of complex heterogeneous materials such ascementitious mortars, soils, rocks or concretes, require a multi-scale approach. The overall characteristics of these materials strongly depend on processes that are occurring at different length scales. Various scale-levels are required to account for the different mechanisms that control the behaviour at different levels of detail. Among the different multi-scale schemes, those based on homogenization procedures are more commonly used due to their versatility. In this research, a consistent homogenized multiscale approach is proposed for modelling mechanical and transport phenomena. A multiscale model, based in the Virtual Element Method (VEM), is implemented in a VEM2 setting. VEM allows for a great flexibility in the mesh, and is a powerful tool to characterize the complex RVEs geometries, reducing the amount of elements needed and hence saving time and resources.